Combining Gene Transfer and Nonhuman Primates to Better Understand and Treat Parkinson’s Disease - Lasbleiz, Christelle; Mestre-Francés, Nadine; Devau, Gina; Luquin, Maria-Rosario; Tenenbaum, Liliane; Kremer, Eric J.; Verdier, Jean-Michel (Frontiers in Molecular Neuroscience, 2019)
Parkinson's disease (PD) is a progressive CNS disorder that is primarily associated with impaired movement. PD develops over decades and is linked to the gradual loss of dopamine delivery to the striatum, primarily through the loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). While the administration of L-dopa and deep brain stimulation are potent therapies, their costs, side effects and gradual loss of efficacy underlines the need to develop other approaches. Unfortunately, the lack of pertinent animal models that reproduce DA neuron loss and behaviour deficits - in a timeline that mimics PD progression - has hindered the identification of alternative therapies. A complementary approach to transgenic animals is the use of nonhuman primates combined with the overexpression of disease-related genes using viral vectors. This approach may induce phenotypes that are not influenced by developmental compensation mechanisms, and that take into account the personality of animals. In this review, we discuss the combination of gene transfer and nonhuman primate to develop “genetic” models of PD that are suitable for testing therapeutic approaches.